English Derivational morphology: Challenges and Teaching Considerations for non-native speakers - Vargas-Vega, Brenda; Mora-Pablo, Irasema (Beyond Words, 2023)
This paper has a twofold purpose: to raise awareness on the complexity of the acquisition of English derivational morphology, and to suggest ways to approach its teaching in the language classroom. Understanding morphology is important because of its impact on other areas of language; however, some authors posit that its explicit instruction is limited in schools. Based on a thorough but comprehensible description of English morphology, we present eight aspects that may be challenging for English Language Learners followed by pedagogical strategies to address them. This way, we hope to offer linguistic insights that can aid the teaching of English as a foreign language and close the gap between linguistic research and the classroom setting.